Surface-enhanced Raman Spectroscopy and Density Functional Theory Study of Glyphosate and Aminomethylphosphonic acid Using Silver Capped Silicon Nanopillars - John Castillo; Ciro Rozo; Kaiyu Wu; Tomas Rindzevicius; Anja Boisen (Universitas Scientiarum)
Glyphosate (GP) is a broad-spectrum systemic herbicide which is used for killing a wide variety of harmful plants. Several recent studies indicate possible adverse health effects on humans. This work is focused on detection and adsorption studies of GP and its metabolite aminomethylphosphonic acid (AMPA) on silver-capped silicon nanopillars using surface-enhanced Raman spectroscopy (SERS). Density Functional Theory with the B3LYP functional was employed for the geometry optimization of ground state geometries and simulation of Raman and SERS spectra of the GP and AMPA. The theoretically calculated and experimentally observed vibrations of GP and AMPA free and attached to the Ag surface exhibited different Raman spectra revealing chemical interactions between the analysed molecules and the metal surface. DFT studies confirmed that the main Ag-GP interaction is with the oxygen from carboxylic and phosphate groups, and for AMPA the main interaction is via a strong interaction between nitrogen from NH with the metal surface. In order to study the binding behavior, adsorption isotherm analysis between GP and AMPA on silver-capped silicon nanopillars (AgNPs) were performed. Finally, the obtained isotherms for GP and AMPA followed a negative cooperative binding mechanism.